Pattern Dot Quantity Affects Auditory Facilitation Effects on Visual Object Representations. (February 2014) - Takeshima, Yasuhiro; Gyoba, Jiro
Auditory stimuli often facilitate visual perception. Audiovisual integration requires spatial and/or temporal proximity between visual and auditory stimuli; additionally, sensory processing speed affects the audiovisual integration process. In the present study we examined the relationship between processing speed and the auditory facilitation effect on visual representations by manipulating dot quantity patterns. We hypothesized that the auditory facilitation effect would be observed in longer interstimulus interval conditions with more dot quantities. This is because more processing time would be required to integrate visual and auditory stimuli. During a backward masking paradigm used in experiment 1, the auditory facilitation effect depended on dot quantity among patterns and the interval between visual stimuli and masks. Moreover, differences in processing time required to integrate visual and auditory stimuli between dot quantities was confirmed from a same-different discrimination task in experiment 2. Therefore, dot quantity affects sensory processing time, and a longer processing time is required for integrating visual and auditory stimuli when visual dot quantity is high.